Spatial density patterns of herbivore response to seasonal dynamics in the tropical deciduous forest of central India. (4th February 2023) - Gupta, Deepti; Krishnamurthy, Ramesh
Abstract: Resource dynamism in seasonal forests leads ungulates to differential habitat preference; hence, their distribution aligns with environmental covariates across spatial and temporal scales. Seasonal patterns of four species of ungulates, namely sambar, chital, nilgai, and wild pig, were investigated and identified as the environmental variables driving the density gradient across two seasons, summer and winter, in the tropical dry deciduous forest of Panna Tiger Reserve, central India. Distance sampling data were analyzed using density surface modeling for ungulates with a survey effort of 518 km in winter and 356 km in summer in a generalized additive modeling framework. We found that season significantly affected the spatial densities of all ungulates, with sambar, chital, and nilgai congregating in summer and wild pig in winter. All ungulates showed a clear seasonal shift to the valley in summer and preferred plateaus in winter. The spatially explicit map outputs draw attention to the seasonal hot spots for ungulates abundance and the species and season‐specific roles of environment variables in defining their distribution. These results provide a scientific basis for direct conservation efforts to the spatially prioritized habitats for cost‐effective management interventions. Abstract : We used a spatio‐temporal model to understand the density distribution of four ungulate species across seasons in dry deciduous forests. We found that species respond spatially and temporally to dynamic environmental conditions.